The conceptual metaphor of animals used for praise and satire in Al Ghaddafi’s discourse - Alhemmair Alwash, Lutfi Mohammed; Abdul Jabar, Mohd Azidan; Nimehchisalem, Vahid; Abdullah, Muhammad Alif Redzuan (Human Resource Management Academic Research Society, 2023)
Metaphor in the local language plays in daily life besides their role in rhetoric and poetry. This work shall focus on the positives and negatives of using the metaphor of animals in Al Ghaddafi’s used animal metaphors in his speeches, under the Cognitive Linguistics and the Critical Metaphor Analysis (CMA). Studies conducted on Classical Arabic metaphors but the focus in this study shall be the concealed meaning. Study objectives are: (1) to unravel the meanings underlying the animal metaphors; (2) to compare similarities, differences, positives and/ or negatives of meanings inspire the animal metaphors in Al Ghaddafi’s discourse. The study adopts qualitative data analysis that uses two comparable corpora as the source of data. The data collection method utilized CMA in order to identify the metaphorical meanings in the semantic meanings. The study also adopted analytical frameworks to analyze the data, namely and, CMA is the theoretical framework (Charters-Black, 2004) that identify and analyze symbols as cognitive instruments. The findings display that the interrelation between these words with the internal states of understanding is not an arbitrary process, but is grounded by a human bodily basis which supports the hypothesis made by (IbarretxeAntuñano, 2002).